Сучасні тенденції маркетингових досліджень у туристичній галузі - Юрченко, Наталія Іванівна; Yurchenko, Nataliia (Харківський національний економічний університет, 2020)
У статті досліджено сучасні тенденцій маркетингових досліджень як складової комплексу маркетингового інструментарію в туристичній сфері. Для досягнення поставленої мети використано такі методи дослідження, як: абстрактно-логічний; ситуаційний аналіз; середніх, абсолютних і відносних величин; порівняння, графічний, соціологічний; статистичний аналіз; економіко-математичний; експертні опитування й оцінки. На основі даних Всесвітньої туристичної організації проаналізовано показники розвитку світового ринку туристичних послуг. Виконано аналіз динаміки кількості суб’єктів туристичної діяльності (туроператорів і турагентів) в Україні; загальної середньооблікової кількості штатних працівників; доходів від надання туристичних послуг; операційних витрат на надання туристичних послуг; кількості туристів, обслугованих туроператорами та турагентами в Україні. Розкрито зміст маркетингових досліджень як багатоетапного процесу, який має включати збирання, реєстрацію й аналіз даних у сфері туристичного бізнесу. Доведено, що маркетингові дослідження в туристичній галузі доцільно проводити систематично. Це дозволить обґрунтовувати й розробляти управлінські рішення з метою максимального задоволення потреб споживачів туристських послуг і вирішувати проблеми значних сезонних коливань попиту. The article is aimed at identifying modern trends of marketing research as part of the complex of marketing instruments in the tourism sphere. To achieve this aim, the article uses the following research methods: abstract-logical; situational analysis; mean, absolute and relative values; comparison, graphic, sociological; statistical analysis; economic-mathematical; expert surveys and estimations. Based on the data of the World Tourism Organization, the indicators of development of the world market of tourist services are analyzed. Performed were the following: analysis of the dynamics of the number of subjects of tourism activity (tour operators and travel agents) in Ukraine; total average number of full-time employees; income from the provision of tourist services; operating expenses for the provision of tourist services; number of tourists served by tour operators and travel agents in Ukraine. The content of marketing research is disclosed as a multi-stage process, which should include the collection, registration and analysis of data in the sphere of tourism business. Marketing researches should be conducted according to 8 stages: determining the problem; development of the concept of research; cabinet marketing research; field market research; analysis of market conditions (supply and demand); research of foreign markets; simulation modeling; formation of a marketing information system. In order to determine the rating of tour operators of the mass segment of the tourism market in 2020, a questionnaire containing 16 questions is specified. Its results can be used when evaluating tour operators in terms of customer comfort and cooperation with travel agents. It is proved that marketing research in the tourism industry is advisable to be carried out systematically. This will provide for substantiating and elaborating managerial solutions in order to maximize the satisfaction of the needs of consumers of tourist services and solve the problems of significant seasonal fluctuations in demand
The Current Trends in Marketing Research in the Tourism Industry
Keywords: туристична галузь; tourism industry; туристична послуга; tourist service; туристичний продукт; tourist product; суб’єкти туристичної діяльності; subjects of tourism activity; кон’юнктура ринку; market conditions; споживачі; consumers; маркетингові дослідження; marketing research; маркетинговий інструментарій; marketing instrumentarium; анкетування; questionnaires; показники; indicators; тенденції; trends; маркетингова стратегія; marketing strategy